SIV antigen immunization induces transient antigen-specific T cell responses and selectively activates viral replication in draining lymph nodes in retroviral suppressed rhesus macaques - Barry Peter A; Clements Janice E; Aye Pyone P; Gama Lucio; Hu Haitao; Lackner Andrew A; Weissman Drew (Retrovirology, 2011)
Abstract Background HIV infection causes a qualitative and quantitative loss of CD4+ T cell immunity. The institution of anti-retroviral therapy (ART) restores CD4+ T cell responses to many pathogens, but HIV-specific responses remain deficient. Similarly, therapeutic immunization with HIV antigens of chronically infected, ART treated subjects results in poor induction of HIV-specific CD4 responses. In this study, we used a macaque model of ART treatment during chronic infection to study the virologic consequences of SIV antigen stimulation in lymph nodes early after immunization. Rhesus CMV (RhCMV) seropositive, Mamu A*01 positive rhesus macaques were chronically infected with SIVmac251 and treated with ART. The immune and viral responses to SIV gag and RhCMV pp65 antigen immunization in draining lymph nodes and peripheral blood were analyzed. Animals were immunized on contralateral sides with SIV gag and RhCMV pp65 encoding plasmids, which allowed lymph nodes draining each antigen to be obtained at the same time from the same animal for direct comparison. Results We observed that both SIV and RhCMV immunizations stimulated transient antigen-specific T cell responses in draining lymph nodes. The RhCMV-specific responses were potent and sustained (50 days post-immunization) in the periphery, while the SIV-specific responses were transient and extinguished quickly. The SIV antigen stimulation selectively induced transient SIV replication in draining lymph nodes. Conclusions The data are consistent with a model whereby viral replication in response to SIV antigen stimulation limits the generation of SIV antigen-specific responses and suggests a potential mechanism for the early loss and poor HIV-specific CD4+ T cell response observed in HIV-infected individuals.